Airborne Laser Scanning (ALS) point clouds of Trail Valley Creek, NWT, Canada (2016) [dataset] - Anders, Katharina; Antonova, Sofia; Boike, Julia; Gehrmann, Martin; Hartmann, Jörg; Helm, Veit; Höfle, Bernhard; Marsh, Philip; Marx, Sabrina; Sachs, Torsten (PANGAEA - Publishing Network for Geoscientific and Environmental Data, 2018)
Anders, Katharina; Antonova, Sofia; Boike, Julia; Gehrmann, Martin; Hartmann, Jörg; Helm, Veit; Höfle, Bernhard; Marsh, Philip; Marx, Sabrina; Sachs, Torsten (2018): Airborne Laser Scanning (ALS) Point Clouds of Trail Valley Creek, NWT, Canada (2016). PANGAEA, https://doi.org/10.1594/PANGAEA.894884, Supplement to: Antonova, Sofia; Thiel, Christian; Höfle, Bernhard; Anders, Katharina; Helm, Veit; Zwieback, Simon; Marx, Sabrina; Boike, Julia (2019): Estimating tree height from TanDEM-X data at the northwestern Canadian treeline. Remote Sensing of Environment, 231, 111251, https://doi.org/10.1016/j.rse.2019.111251